Low-dose radiotherapy for COVID-19 pneumonia and cancer: summary of a recent symposium and future perspectives. (1st February 2023) - Little, Mark P.; Zhang, Wei; van Dusen, Roy; Hamada, Nobuyuki; Bugden, Michelle; Cao, Meiyun; Thomas, Kiersten; Li, Deyang; Wang, Yi; Chandrashekhar, Megha; Khan, Mohammad K.; Coleman, C. Norman
Abstract: The lessons learned from the Coronavirus Disease 2019 (COVID-19) pandemic are numerous. Low dose radiotherapy (LDRT) was used in the pre-antibiotic era as treatment for bacterially/virally associated pneumonia. Motivated in part by these historic clinical and radiobiological data, LDRT for treatment of COVID-19-associated pneumonia was proposed in early 2020. Although there is a large body of epidemiological and experimental data pointing to effects such as cancer at low doses, there is some evidence of beneficial health effects at low doses. It has been hypothesized that low dose radiation could be combined with immune checkpoint therapy to treat cancer. We shall review here some of these old radiobiological and epidemiological data, as well as the newer data on low dose radiation and stimulated immune response and other relevant emerging data. The paper includes a summary of several oral presentations given in a Symposium on "Low dose RT for COVID and other inflammatory diseases" as part of the 67th Annual Meeting of the Radiation Research Society, held virtually 3-6 October 2021.